Metabolic improvement after exercise training in children with obesity: Possible role of the six-minute walking test - Luca Giovanelli; Giuseppina Bernardelli; Simone Facchetti; Mara Malacarne; Matteo Vandoni; Vittoria Carnevale Pellino; Gianvincenzo Zuccotti; Valeria Calcaterra; Daniela Lucini (PLoS ONE, 2025)
The aims of this study are to evaluate the effectiveness of an online supervised training program in modulating lipid and glucose metabolism in children with obesity and to investigate the possible role of the 6-minute walking test (6MWT) as a predictor of metabolic improvement. A total of 35 Caucasian children with obesity (aged 8-13) were enrolled in the study and tested before (T0) and after (T1) a 12-week online supervised exercise training protocol: cardiovascular fitness (by means of 6MWT), metabolic biochemical profile, lifestyle (with ad hoc questionnaires focusing on physical activity, nutrition, sedentariness, sleep hours and quality, health perception) and Cardiac Autonomic Regulation (CAR) were assessed. Spearman correlations between the variations in the studied outcomes were explored. After intervention, the distance covered during 6MWT significantly increased (p < 0.001), and nutrition quality improved slightly but significantly (p = 0.03). The improvement in the 6MWT performance was shown to be significantly correlatee with the reduction of insulin levels (r = -0.455; p = 0.02), HOMA-IR Index (r = -0.452; p = 0.02), total cholesterol values (r = -0.549; p = 0.004) and Atherogenic Index of Plasma (AIP) (r = 0.422; p = 0.04). Moreover, there was a significant correlation between the improvement in 6MWT and health perception (r = 0.578; p = 0.002). We observed that the improvement in the 6MWT performance correlates with better metabolic profile after exercise training in children with obesity suggesting the goodness of this simple test on unveil changes in pathogenetic processes underlying obesity.